(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Abstract Pesantren is convinced as the oldest education institution inIndonesia. From its historical development, there are three kinds of pesantrens which are being as the product of social change occured. This research did as response and effort to know more about any contribution od pesantren to society, especially dealing with religious education services. Supposedly, in dinamic society nowadays, pesantrens give services which are different amomg types. This can be proved by the results of this research that peantren salaf tends to be tafaqquh fiddin type, whereas pesantren khalaf and combination tend to a modern system type.